Binge-watching: addiction or entertainment - Mukhitova, G.M. (KAZGUU Liberal Arts Digest Volume 1. M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2021)
Binge-watching is a new type of consuming video content such as TV programs, TV series, and Video- On-Demand platforms. The purpose of this paper is analyzing selected literature in order to differentiate between positive and negative aspects of binge- watching. By reviewing the articles written by psychological and medical researches, has been found that frequent practice of binge-watching leads to an addictive behavior.
Keywords: binge-watching, Video-On-Demand platforms, addictive behavior